Complete Sequence and Analysis of Plastid Genomes of Two Economically Important Red Algae: Pyropia haitanensis and Pyropia yezoensis - Wang, Li; Mao, Yunxiang; Kong, Fanna; Li, Guiyang; Ma, Fei; Zhang, Baolong; Sun, Peipei; Bi, Guiqi; Zhang, Fangfang; Xue, Hongfan; Cao, Min (PLOS ONE, 2013)
Background Pyropia haitanensis and P. yezoensis are two economically important marine crops that are also considered to be research models to study the physiological ecology of intertidal seaweed communities, evolutionary biology of plastids, and the origins of sexual reproduction. This plastid genome information will facilitate study of breeding, population genetics and phylogenetics. Principal Findings We have fully sequenced using next-generation sequencing the circular plastid genomes of P. hatanensis (195,597 bp) and P. yezoensis (191,975 bp), the largest of all the plastid genomes of the red lineage sequenced to date. Organization and gene contents of the two plastids were similar, with 211–213 protein-coding genes (including 29–31 unknown-function ORFs), 37 tRNA genes, and 6 ribosomal RNA genes, suggesting a largest coding capacity in the red lineage. In each genome, 14 protein genes overlapped and no interrupted genes were found, indicating a high degree of genomic condensation. Pyropia maintain an ancient gene content and conserved gene clusters in their plastid genomes, containing nearly complete repertoires of the plastid genes known in photosynthetic eukaryotes. Similarity analysis based on the whole plastid genome sequences showed the distance between P. haitanensis and P. yezoensis (0.146) was much smaller than that of Porphyra purpurea and P. haitanensis (0.250), and P. yezoensis (0.251); this supports re-grouping the two species in a resurrected genus Pyropia while maintaining P. purpurea in genus Porphyra. Phylogenetic analysis supports a sister relationship between Bangiophyceae and Florideophyceae, though precise phylogenetic relationships between multicellular red alage and chromists were not fully resolved. Conclusions These results indicate that Pyropia have compact plastid genomes. Large coding capacity and long intergenic regions contribute to the size of the largest plastid genomes reported for the red lineage. Possessing the largest coding capacity and ancient gene content yet found reveal that Pyropia are more primitive multicellular red algae.